ANALISIS PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN KAMPUNG WISATA KREATIF DESA SEKIDA KECAMATAN JAGOI BABANG - Nana Novita Pratiwi (Universitas Islam Sultan Agung Semarang, 2021)
Sekida Village as a Creative Tourism Village is an embryo for the community's economic development. The Creative Tourism Village has provided a space for participation for the community through various activities. Thus, this study aims to determine forms of community participation in supporting the development of the Creative Tourism Village in Sekida Village. The research approach used is phenomenological with qualitative descriptive method. The research stages consisted of data collection, data reduction, data presentation and drawing conclusions. The results of the analysis concluded that the largest form of community participation was manpower and expertise with a percentage of 82% and 72%, respectively. Based on their characteristics, the people who are dominant in contributing to supporting the development of the Creative Tourism Village through their participation are the older adults with an elementary education level.Keywords: Community Participation, Creative Tourism Village, Sekida Village.